Valve‐in‐valve transcatheter aortic valve replacement versus redo surgical aortic valve replacement: A systematic review and meta‐analysis. Issue 7 (2nd April 2021) - Ahmed, Adham; Levy, Kenneth H.
Abstract: Background/Aim: With the growing contemporary use of bioprosthetic valves, whose limited long‐term durability has been well‐documented, an increase in the need for reintervention is expected. We perform a meta‐analysis to compare the current standard of care, redo surgical aortic valve replacement (Redo SAVR) with the less invasive alternative, valve‐in‐valve transcatheter aortic valve replacement (ViV TAVR) for treating structural valve deterioration. Methods: After a comprehensive literature search, studies comparing ViV TAVR to Redo SAVR were pooled to perform a pairwise meta‐analysis using the random‐effects model. Primary outcomes were 30‐day and follow‐up mortality. Results: A total of nine studies including 9127 patients were included. ViV TAVR patients were significantly older (mean difference [MD], 5.82; p  = .0002) and more frequently had hypercholesterolemia (59.7 vs. 60.0%; p  = .0006), coronary artery disease (16.1 vs. 16.1%; p  = .04), periphery artery disease (15.4 vs. 5.7%; p  = .004), chronic obstructive pulmonary disease (29.3 vs. 26.2%; p  = .04), renal failure (30.2 vs. 24.0%; p  = .009), and >1 previous cardiac surgery (23.6 vs. 15.9%; p  = .004). Despite this, ViV TAVR was associated with decreased 30‐day mortality (OR, 0.56; p  < .0001). Conversely, Redo SAVR had lower 30‐day paravalvular leak (OR, 6.82; p  = .04), severe patient‐prosthesis mismatch (OR, 3.77; p  < .0001), and postoperative aortic valve gradients (MD, 5.37; p  < .0001). There was no difference in follow‐up mortality (HR, 1.02; p  = .86). Conclusions: Despite having patients with an increased baseline risk, ViV TAVR was associated with lower 30‐day mortality, while Redo SAVR had lower paravalvular leak, severe patient‐prosthesis mismatch, and postoperative gradients. Although ViV TAVR remains a feasible treatment option in high‐risk patients, randomized trials are necessary to elucidate its efficacy over Redo SAVR.